Front Cover: PorphyStruct: A Digital Tool for the Quantitative Assignment of Non‐Planar Distortion Modes in Four‐Membered Porphyrinoids (Chem. Eur. J. 45/2021). Issue 45 (26th June 2021) - Krumsieck, Jens; Bröring, Martin
Abstract : PorphyStruct is a new digital tool that allows quick and easy analyses of hidden conformational features of porphyrinoids from structural data. The software introduces the well‐established technique of normal‐mode structural decomposition (NSD) to porphyrinoids like the corroles, and while retaining the terminology of the NSD method, it is flexible with respect to the size and shape of the macrocycle perimeter. The cover image shows the utopia of a futuristic analysis laboratory where life‐size molecules are analysed for such hidden structural characteristics. More information can be found in the Full Paper by J. Krumsieck and M. Bröring. (DOI: 10.1002/chem.202101243 ).